Spatially resolved multi-omics analysis of indigenous Bacillus-fortified high-temperature Daqu - Hao Shi; Yuling Shen; Qingqing Ye; Hui Yu; Maoling Tian; Hongmei Wang; Yang Wei; Shiying Yan; Yiping Chen; Jie Zhang; Shu Li; Yang Yang; et al. (Food Research International, 2026)

Three-dimensional thermal management: Biomass aerogel with super-hydrophilicity for high-efficiency solar evaporation via environmental energy synergy - Li Jiang; Yanyou Huang; Liangdong Ye; Yuling Lv; Ruibin Shen; Wei Wang; Yanlan Pan; Zuocai Zhang; Shaorong Lu (Desalination, 2026)

A 3D porous KCuFC/collagen fibers/gelatin adsorbent for ultra-fast cesium capture from radioactive wastewater - Xiaoxia Ye; Shanyuan Chen; Juan Liu; Yuling Tang; Jianfei Zhou; Wei Luo; Jie Chen (Bioresource Technology, 2026)

Wheat properties shape microbial succession and flavor profile in high-temperature Daqu fermentation: a multi-omics perspective - Hongmei Wang; Yuling Shen; Sican Luo; Yongxin Hu; Fuli Wen; Qian Wang; Xi Shen; Hao Shi; Yiping Chen; Xiaozhong Zhong; Songtao Wang; Yang Wei; et al. (Food Research International, 2026)

An FcRn-mediated exosome-based oral vaccine enhanced co-mucosal immunity via targeting intestinal epithelial transport and lymphatic activation - Wei Zhang; Wen Guo; Caishun Chen; Meiqi Han; Yuling Mao; Siling Wang (Chemical Engineering Journal, 2026)

Mechanistic insights into the pore-scale transport and retention of microplastics: bridging physical and geochemical controls - Yaqiang Wei; Jian Liang; Yiran Chen; Jiao Zhang; Zaiyong Zhang; Ying Lyu; Zi Zhan; Yu Li; Jialun Xie; Yuling Chen; Hui Li (Water Research, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Effect of heat-moisture modified sweet potato starch on the microstructure and physicochemical properties of wheat noodles - Wei Wang; Dongdong Huang; Yuling Ma; Yiying Yang; Aijun Hu; Haiyan Gao (Journal of Cereal Science, 2026)

Plitidepsin induces apoptosis in glioma cells through β-TrCP-mediated ubiquitination and degradation of BMI1 - Yiting Wei; Yuling Wan; Shilong Duan; Fanyong Gong; Yuewei Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Assessing coastal groundwater risks from nuclear-contaminated water discharge under extreme drought and sustainable recharge solutions - Jiao Zhang; Yaqiang Wei; Yuling Chen; Zhenzhong Hu; Damià Barceló; Tian-Chyi Jim Yeh; Jiazhong Qian; Bradley A. Weymer; Zi Zhan; Xinde Cao; Hui Li (Journal of Contaminant Hydrology, 2026)

Novel inter-cable wire rope dampers for hanger cable vibration control: Experiment, FE modeling method, and Field test - Shilong Yang; Keyu Lai; Wei Fan; Yuling Liu; Zhiheng Chen; Zhengqing Chen (Engineering Structures, 2026)

Elevated CO2 synergizes with nanoplastics to intensify arsenic mobilization, biotransformation, and plant uptake in soil-spinach systems - Wei Li; Yabo Wang; Yuling Suo; Zishu Zheng; Qiao Xu; Meiling Xu; Fen Xu; Weiqin Yin; Shengsen Wang; Xiaozhi Wang (Environmental Pollution, 2026)

Ameliorative Effects of an Antioxidant and Anti-Inflammatory Limosilactobacillus fermentum TG017 on DSS-Induced Ulcerative Colitis in Mice - Qianhao Hou; Yuling Li; Zuanyuan Huang; Honghua Hu; Xin Li; Jinyuan Zhang; Wenying Duan; Songsong Pan; Zetian Wang; Xiaodong Liu; Wei Xu; Lijun Liao (Probiotics and Antimicrobial Proteins, 2026)

Evidence for Early Middle Jurassic wildfires: New macro-charcoal records from the Xishanyao Formation, Junggar Basin, Northern Xinjiang, China - Bing Yang; Yuling Na; Xiao Shi; Yi Wei; Xinzhi Zhang; Bing Wang; Siyuan Sun; Weitong Li (Review of Palaeobotany and Palynology, 2026)

Stretchable multifunctional composite films with ultra-high conductivity for sustainable heating, EMI shielding, and antimicrobial applications - Yuling Lv; Yanyou Huang; Liangdong Ye; Ruibing Shen; Li Jiang; Wei Wang; Shaorong Lu (Chemical Engineering Journal, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Biomass organohydrogel toward green wearable sensors: Enhancing high and low temperature sensing properties, UV shielding properties, and long-term cycling durability - Ruibing Shen; Qiaoyan Wei; Liangdong Ye; Liling Zhang; Yanyou Huang; Yuling Lv; Ziwei Li; Zuocai Zhang; Xiaokun Han; Shaorong Lu (Chemical Engineering Journal, 2026)

Combining deep learning and protein engineering to develop a thermostable protease for aquafeed applications - Zipeng Wu; Yuling Wang; Yiran Lao; Yutong Gao; Lingjie Kong; Han Jiang; Yuyang Zou; Peizhi Gu; Mingtao Huang; Xiufang Liu; Tao Wei (Food Bioscience, 2025)

Genome-wide identification and functional analysis of the polyamine metabolism-related genes in Foxtail millet (Setaria Italica L.) - Liuan Hao; Tao Wang; Yangyang Wei; Pengtao Li; Yuling Liu; Quanwei Lu; Huawen Zou; Renhai Peng (Functional & Integrative Genomics, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

A sequential HT-Bayesian method offers deep insights for precise groundwater contaminant characterization - Hui Li; Zi Zhan; Yuling Chen; Tian-chyi Jim Yeh; Yiran Chen; Jiao Zhang; Yaqiang Wei (Water Research, 2025)

Analysis of metabolic characteristics of highly resistant grass carp bred on the basis of constitutive expression level of innate immune molecules - Yuling Wei; Bin Li; Zhe Long; Zongjun Du; Zhao Lv; Tiaoyi Xiao (Fish & Shellfish Immunology, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

Fluorine-decorated rare-earth hydroxides mediated preparation of hollow low-iridium oxyfluoride for highly efficient oxygen evolution reaction catalyst - Yuling Hu; Zhen Zeng; Yun Liu; Hao Zhang; Wenjuan Shi; Zhengye Kang; Yuliang Yuan; Wei Sun; Xinlong Tian (Chemical Engineering Journal, 2025)

The impact of COVID-19 pandemic on the etiological spectrum of respiratory infections in children - Jing Wang; Yuling Han; Xiaoling Wei; Yanqin Liu; Hua Zhang; Xiang Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Seawater intrusion angle controls colloidal chromium migration across coastal groundwater interfaces - Yaqiang Wei; Jiao Zhang; Yuling Chen; Chengpeng Yuan; Xinde Cao (Journal of Hazardous Materials, 2025)

Cobalt-doped zinc phosphides regulated by phytic acid effects on the electrochemical activity of sensing clothianidin - Peiyuan Wei; Wei Han; Lingling Xie; Hongjun Chen; Yuling Wang; Limin Zhu; Baoshan He; Xiaoyu Cao (Chemical Engineering Journal, 2025)

First report of Fusarium fujikuroi causing leaf blight on Chinese yew - Yao Charles Meto; Guoyu Wei; Huayang Xu; Yuling Jiang; Hongfei Gao; Anlong Hu (Crop Protection, 2025)

Human FABP7 selectively captures docosahexaenoic acid over eicosapentaenoic acid: A potential protein-based platform for affinity purification of ω-3 lipids - Yuling Tang; Xunjiao Wei; Yonghua Wang; Wen Chen (Food Bioscience, 2025)

Portable aptasensor for smartphones using trimetallic PtPdAuNFs and triplex molecular switch for rapid detection of procymidone - Ruonan Wang; Baoshan He; Zhengyong Liang; Yuling Wang; Huali Jin; Min Wei; Wenjie Ren; Zhiguang Suo; Yiwei Xu (Chemical Engineering Journal, 2025)

Molecular Characterization and Antiviral Function Against GCRV of Complement Factor D in Barbel Chub (Squaliobarbus curriculus) - Yu Xiao; Zhao Lv; Yuling Wei; Mengyuan Zhang; Hong Yang; Chao Huang; Tiaoyi Xiao; Yilin Li (Fishes, 2025)
The barbel chub (Squaliobarbus curriculus) exhibits remarkable resistance to grass carp reovirus (GCRV), a devastating pathogen in aquaculture. To reveal the molecular basis of this resistance, we investigated complement factor D (DF)—a rate-limiting serine protease governing alternative complement pathway activation. Molecular cloning revealed that the barbel chub DF (ScDF) gene encodes a 1251-bp cDNA sequence translating into a 250-amino acid protein. Crucially, bioinformatic characterization identified a unique N-glycosylation site at Asn139 in ScDF, representing a structural divergence absent in grass carp (Ctenopharyngodon idella) DF (CiDF). While retaining a conserved Tryp_SPc domain harboring the catalytic triad (His61, Asp109, and Ser204) and substrate-binding residues (Asp198, Ser219, and Gly221), sequence and phylogenetic analyses confirmed ScDF’s evolutionary conservation, displaying 94.4% amino acid identity with CiDF and clustering within the Cyprinidae. Expression profiling revealed constitutive ScDF dominance in the liver, and secondary prominence was observed in the heart. Upon GCRV challenge in S. curriculus kidney (SCK) cells, ScDF transcription surged to a 438-fold increase versus uninfected controls at 6 h post-infection (hpi; p

Mineral-element-chelating activity of food-derived peptides: influencing factors and enhancement strategies - Chaonan Cai; Yuting Liu; Yuling Xu; Juntao Zhang; Benmei Wei; Chengzhi Xu; Haibo Wang (Critical Reviews in Food Science and Nutrition, 2025)

Afforestation increases glomalin-related soil protein content and enhances its association with stable soil carbon in karst regions - Lei Xie; Qiumei Ling; Peilei Hu; Yuling Zhang; Wei Zhang; Yuan Zhao; Kelin Wang (Forest Ecology and Management, 2025)

The structural characteristics and expression characteristics of C1S in response to GCRV infection in grass carp - Yuling Wei; Zhao Lv; Zongjun Du; Tiaoyi Xiao (Fish & Shellfish Immunology, 2025)

Superoxide anion radicals mediated degradation of tetrachloropicolinic acid in biochars-Fe P@Fe-FexC/O2 system with excellent reactivity durability - Hongyun Niu; Shaojie Shi; Siyu Zhu; Yuling He; Qiwen An; Hao Ding; Xuwenqi Zhang; Dongbin Wei; Yali Shi; Yaqi Cai (Water Research, 2025)

A self-reinforcing, self-healing, and shape memory polybutadiene-based polyurethane via disulfide bonds for healable flexible sensors - Haolei Shi; Yu Shi; Liping Ren; Wei Zhang; Yuan Ji; Jichi Zhang; Xu Zhong; Yuling Liang; Jidong Dong; Yadong Wu; Wei Li; Dawei Zhang; et al. (Chemical Engineering Journal, 2025)

A high-static-low-dynamic stiffness wire rope isolator with a magnetic negative stiffness device: Experiment, analytical method, and optimization - Shilong Yang; Wei Fan; Yuling Liu; Lingfei Ma; Zhengqing Chen (Engineering Structures, 2025)

Influences of natural organic acids on the degradation of atrazine in water by pyrite-mediated Fenton oxidation - Yuling Zheng; Fang Li; Chen Yan; Wei Yang; Jia Wen; Biao Song (Journal of Water Process Engineering, 2025)

Technological progress accelerates CO2 emissions peaking in a megacity: Evidence from Shanghai, China - Wei Li; Zhenjie Chen; Manchun Li; Yuling Wen (Sustainable Cities and Society, 2025)

Effects of long-term exposure to sulfamethoxazole on the sediments in sewage pipe: Extracellular polymeric substance, microbial communities, and antibiotic resistance genes - Yang Tao; Changfeng Zhou; Yuling Xie; Aoxi Chen; Kunyu Liu; Xin Wu; Haodong Wei; Cuiyun Liu (Journal of Environmental Chemical Engineering, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

Eliminating the effect of pH: Dual-matrix modulation adsorbent enables efficient lithium extraction from concentrated seawater - Yu Han; Liuqian An; Yan Yang; Yuling Ma; Hongliang Sun; Jinxin Yao; Tao Zhang; Wei Wang (Water Research, 2025)

Quantitative study on the relationship between land use and land cover and diatom community in urban streams - Xiang Chen; Weiqi Zhou; Wenjuan Yu; Mingwei Yang; Dong Sheng; Kangyong Li; Na Li; Yuling Ou; Feng Wei (Environmental Science and Pollution Research, 2024)

Selective ion channel adsorbents facilitate efficient and low environmental impact extraction of liquid lithium resources - Yu Han; Yan Yang; Yuling Ma; Daxin Liang; Liping Wen; Jun Ma; Wei Wang (Journal of Hazardous Materials, 2024)

Study on the physical properties of red clay cured by different external admixtures combined with enzyme induced carbonate precipitation technology - Yu Song; Yuling Chen; Jichun Cheng; Wei Liu; Jiaqi Li; Jianwei Zhang; Junjie Zheng (Carbonates and Evaporites, 2024)

Simultaneous removal of cadmium and arsenic co-contamination by iron/sulfur-modified zeolites combined with sulfate-reducing bacteria - Wei Yang; Jia Wen; Yichen Zhou; Wenxing Cheng; Yuling Zheng (Journal of Water Process Engineering, 2024)

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Simultaneous removal of CTRX and Cr(Ⅵ) by CQDs-doped bifunctional molecular imprinted BiOCl/Bi3NbO7 photocatalyst: The enhanced selective performance and charge separation abilities - Huining Zhang; Yankui Xiao; Zongqian Zhang; Jianping Han; Zhiguo Wu; Zhiqiang Wei; Ying Zhu; Qi Guo; Lihong Tian; Yuling Tang (Journal of Environmental Chemical Engineering, 2024)

Preparation, bioactivities, and food industry applications of tuber and tuberous roots peptides: A review - Mengjia Zhu; Fei Li; Yuling Zhang; Jia Yu; Yuxi Wei; Xiang Gao (Food Chemistry, 2024)

A pH transformable nanocarrier for gradual and precise delivery of a natural immunomodulator and chemotherapy agent to trigger tumor apoptosis - Qianwen Sun; Wei Chen; Qi Zhang; Yanqi Han; Yue Gao; Jun Ye; Hongliang Wang; Yi Zhang; Lili Gao; Yuling Liu; Yanfang Yang (Chemical Engineering Journal, 2024)

Effects of ocean acidification and nitrogen limitation on the growth and photophysiological performances of marine macroalgae Gracilariopsis lemaneiformis - Yuling Yang; Wei Li; Yahe Li; Nianjun Xu (Frontiers in Marine Science, 2024)
To investigate the effects of ocean acidification (OA) and nitrogen limitation on macroalgae growth and photophysiological responses, Gracilariopsis lemaneiformis was cultured under two main conditions: ambient (Low CO 2 , LC, 390 μatm) and CO 2 enriched (High CO 2 , HC, 1000 μatm), with low (LN, 7 μmol L -1 ) and high (HN, 56 μmol L -1 ) nitrate. High CO 2 levels decreased growth under both LN and HN treatments. HC reduced Chl a , carotenoids, phycoerythrin (PE), and phycocyanin (PC) under HN conditions, while only Chl a decreased under LN conditions. NO 3 - uptake rate was restricted under LN compared to HN, while HC enhanced it under HN. Net photosynthetic O 2 evolution rates did not differ between CO 2 and nitrate treatments. Dark respiration rates were higher under HN, further boosted by HC. The stimulated effective quantum yield (Y(II)) corresponded to decreased non-photochemical quenching (NPQ) under HN conditions. Nitrate, not CO 2 , showed significant effects on the relative electron transport rate (rETR max ), light use efficiency (α) and saturation light intensity (I k ) that with lowered rETR max and α under LN culture. Our results indicate that OA may negatively affect Gracilariopsis lemaneiformis growth and alter its photophysiological performance under different nutrient conditions.

Effects of low-molecular-weight organic acids on the transformation and phosphate retention of iron (hydr)oxides - Yu Liang; Jing Liu; Jiezi Jin; Yuling Han; Zhiyuan Wei (Science of The Total Environment, 2024)

The role of MASP1 in the complement system and expression characteristics in response to GCRV infection in grass carp - Yuling Wei; Zhao Lv; Tiaoyi Xiao; Zongjun Du (Fish & Shellfish Immunology, 2024)

Effects of soil aggregates and minerals on microbial necromass carbon are regulated by parent materials - Lei Xie; Peilei Hu; Qiumei Ling; Wei Zhang; Pengpeng Duan; Yuling Zhang; Kelin Wang (Applied Soil Ecology, 2024)

Eliminating adverse effects of fouling layer using composite membranes with dense surface layers for sustainable membrane distillation of high-strength wastewater - Peizhi Wang; Jiawei Cheng; Jinxin Yao; Yuling Ma; Chuandong Wu; Dan Song; Wei Cheng; Jun Ma; Wei Wang (Desalination, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

Photocatalytic removal of ammonia nitrogen from water: investigations and challenges for enhanced activity - Huining Zhang; Yang Cao; Shaofeng Wang; Yuling Tang; Lihong Tian; Wenrui Cai; Zhiqiang Wei; Zhiguo Wu; Ying Zhu; Qi Guo (Environmental Science and Pollution Research, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Plowing drag-adaptive operation control method based on motor temperature compensation for electric tractor - Qi Wang; Xudong Wang; Wei Wang; Yongjie Cui; Yuling Song (Journal of Terramechanics, 2024)

A new approach of simultaneous adsorption and regeneration of activated carbon to address the bottlenecks of pharmaceutical wastewater treatment - Weichen Qin; Yuling Dong; Huan Jiang; Wei Hao Loh; Joseph Imbrogno; Tim M. Swenson; Orlando Garcia-Rodriguez; Olivier Lefebvre (Water Research, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

"Needle" hidden in silk floss: Inactivation effect and mechanism of melamine sponge loaded bismuth oxide composite copper-metal organic framework (MS/Bi2O3@Cu-MOF) as floating photocatalyst on Microcystis aeruginosa - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Hazardous Materials, 2024)

Research progress and trend of antibiotics degradation by electroactive biofilm: A review - Xinyi Zhang; Yuling Xu; Yanyan Liu; Yushan Wei; Feng Lan; Renjun Wang; Yuewei Yang; Junfeng Chen (Journal of Water Process Engineering, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Long-term effectiveness and sustainability of EHC remediation in carbon tetrachloride-contaminated groundwater: Mechanistic understanding and practical applications - Liu Ling; Yaqiang Wei; Haobo Niu; Hang Zhao; Yuling Chen; Dan Qu; Miao Gao; Jian Chen (Journal of Cleaner Production, 2024)

The double heterostructure photocatalyst MoS2@ZIF-67/TiO2: Triumphant modification of TiO2 and efficient removal of Karenia mikimotoi - Yushan Wei; Junfeng Chen; Mengjiao Wang; Xinyi Zhang; Yuling Xu; Qingying Wei; Feng Lan; Peike Gao; Yanyan Liu; Renjun Wang (Chemical Engineering Journal, 2024)

Improving oxygen reduction reaction by cobalt iron-layered double hydroxide layer on nickel-metal organic framework as cathode catalyst in microbial fuel cell - Xinyi Zhang; Yuling Xu; Yanyan Liu; Yushan Wei; Feng Lan; Jiayu Wang; Xuemeng Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Well-known polypeptides of deer antler velvet with key actives: modern pharmacological advances - He Sun; Dandan Xiao; Wei Liu; Xue Li; Zhe Lin; Yong Li; Yuling Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Research status and prospects of organic photocatalysts in algal inhibition and sterilization: a review - Yushan Wei; Renjun Wang; Mengjiao Wang; Lijun Hu; Xinyi Zhang; Yuling Xu; Yanyan Liu; Feng Lan; Junfeng Chen (Environmental Science and Pollution Research, 2023)

The selection of floating photocatalyst carrier and algae inhibition effect of Karenia mikimotoi based on SNP-TiO2@Cu-MOF under visible light - Renjun Wang; Lijun Hu; Mengjiao Wang; Yushan Wei; Yuling Xu; Xinyi Zhang; Junfeng Chen (Chemosphere, 2023)

Joint control method based on speed and slip rate switching in plowing operation of wheeled electric tractor equipped with sliding battery pack - Qi Wang; Xudong Wang; Wei Wang; Yuling Song; Yongjie Cui (Computers and Electronics in Agriculture, 2023)

Research progress and prospect of metal-organic framework and covalent-organic framework for photocatalytic treatment of harmful algal blooms - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Water Process Engineering, 2023)

Structural comparison and expression function analysis of BF/C2 in Ctenopharyngodon idella and Squaliobarbus curriculus - Yuling Wei; Zhao Lv; Qiaolin Liu; Jianbo Yu; Yu Xiao; Zongjun Du; Tiaoyi Xiao (Fish & Shellfish Immunology, 2023)

Transformation of sulfur in the sediment–water system of the sewage pipeline under different hydraulic retention time - Cuiyun Liu; Haodong Wei; Qi Liu; Yang Tao; Yuling Xie; Changfeng Zhou (Environmental Pollution, 2023)

Quantitative Assessment of Monitoring Natural Attenuation on Carbon Tetrachloride Reduction at a Groundwater-Contaminated Site in Eastern China - Yaqiang Wei; Weijiang Liu; Ling Liu; Haobo Niu; Lu Li; Yuling Chen; Jian Chen (Water, Air, & Soil Pollution, 2023)

Trace N-doped manganese dioxide cooperated with Ping-pong chrysanthemum-like NiAl-layered double hydroxide on cathode for improving bioelectrochemical performance of microbial fuel cell - Yuling Xu; Xinyi Zhang; Yanyan Liu; Yushan Wei; Feng Lan; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2023)

Can natural resource rent, technological innovation, renewable energy, and financial development ease China's environmental pollution burden? New evidence from the nonlinear-autoregressive distributive lag model - Haojie Liao; Yuqiang Chen; RongYong Tan; Yuling Chen; Xiaoyu Wei; Hongmei Yang (Resources Policy, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Boron doping g-C3N4 supported Cu2O for photocatalytic reforming of xylose into lactic acid - Yanting Lv; Weiyong Shao; Yuling Kong; Nanhua Li; Xinrui Huang; Zhihao Tang; Murong Gong; Lizi Li; Weiqi Wei (Journal of Environmental Chemical Engineering, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

Premature mortality attributable to NO2 exposure in cities and the role of built environment: A global analysis - Jian Song; Yuling Wang; Qin Zhang; Wei Qin; Rubing Pan; Weizhuo Yi; Zhiwei Xu; Jian Cheng; Hong Su (Science of The Total Environment, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

Pollution in river tributaries restricts the water quality of ecological water replenishment in the Baiyangdian watershed, China - Xu Yao; Zheng Wang; Wei Liu; Yao Zhang; Tianhe Wang; Yuling Li (Environmental Science and Pollution Research, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Photocatalytic degradation effect and mechanism of Karenia mikimotoi by non-noble metal modified TiO2 loading onto copper metal organic framework (SNP-TiO2@Cu-MOF) under visible light - Lijun Hu; Junfeng Chen; Yushan Wei; Mengjiao Wang; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Journal of Hazardous Materials, 2023)

Heterogeneous interfacial photocatalysis for the inactivation of Karenia mikimotoi by Bi2O3 loaded onto a copper metal organic framework (Bi2O3@Cu-MOF) under visible light - Mengjiao Wang; Junfeng Chen; Lijun Hu; Yushan Wei; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Chemical Engineering Journal, 2023)

Effects of roasting and deodorisation on 3-monochloropropane-1, 2-diol esters, 3, 4-benzopyrene and trans fatty acids in peanut oil - Pan Gao; Yuling Zheng; Hui Liu; Wei Yang; Chuanrong Hu; Dongping He (Food Additives & Contaminants: Part A, 2022)

The relative importance of soil moisture in predicting bacterial wilt disease occurrence - Gaofei Jiang; Ningqi Wang; Yaoyu Zhang; Zhen Wang; Yuling Zhang; Jiabao Yu; Yong Zhang; Zhong Wei; Yangchun Xu; Stefan Geisen; Ville-Petri Friman; Qirong Shen (Soil Ecology Letters, 2021)

Spatial-temporal dynamics and scenario simulation of land ecological security: a case study of Deyang, Sichuan Province, China - Wei He; YuLing Wen; ZhongQing Xiong (Environmental Science and Pollution Research, 2021)

Travel Behaviours of Sharing Bicycles in the Central Urban Area Based on Geographically Weighted Regression: The Case of Guangzhou, China - Zongcai Wei; Feng Zhen; Haitong Mo; Shuqing Wei; Danli Peng; Yuling Zhang (Chinese Geographical Science, 2021)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

MiR-153 regulates cardiomyocyte apoptosis by targeting Nrf2/HO-1 signaling - Xianting Zhu; Yuling Zhao; Wei Hou; Ling Guo (Chromosome Research, 2019)

The contribution of oxygen-containing functional groups to the gas-phase adsorption of volatile organic compounds with different polarities onto lignin-derived activated carbon fibers - Fanyue Meng; Min Song; Yuexing Wei; Yuling Wang (Environmental Science and Pollution Research, 2019)

Exogenous salicylic acid regulates reactive oxygen species metabolism and ascorbate–glutathione cycle in Nitraria tangutorum Bobr. under salinity stress - Yongqing Yan; Chenhui Pan; Yuling Du; Danyang Li; Wei Liu (Physiology and Molecular Biology of Plants, 2018)

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

Emotional intelligence moderates the relationship between regional gray matter volume in the bilateral temporal pole and critical thinking disposition - Xiaonan Yao; Shuge Yuan; Wenjing Yang; Qunlin Chen; Dongtao Wei; Yuling Hou; Lijie Zhang; Jiang Qiu; Dong Yang (Brain Imaging and Behavior, 2018)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Effects of seawater acidification on the growth rates of the diatom Thalassiosira (Conticribra) weissflogii under different nutrient, light, and UV radiation regimes - Wei Li; Yuling Yang; Zhenzhen Li; Juntian Xu; Kunshan Gao (Journal of Applied Phycology, 2017)

Expression profile of human immune-responsive gene 1 and generation and characterization of polyclonal antiserum - Wei Xiao; Lan Wang; Ruijing Xiao; Mengjun Wu; Jinquan Tan; Yuling He (Molecular and Cellular Biochemistry, 2011)

Production of diosgenin from yellow ginger (Dioscorea zingiberensis C. H. Wright) saponins by commercial cellulase - Wei Liu; Wen Huang; WeiLing Sun; YuLing Zhu; JinRen Ni (World Journal of Microbiology and Biotechnology, 2010)

Molecular cloning, sequence and expression analysis of ZmArf2, a maize ADP-ribosylation factor - Yanyang Liu; Junzhou Li; Yuling Li; Mengguan Wei; Qingxin Cui; Qilei Wang (Molecular Biology Reports, 2010)

QTL identification of grain protein concentration and its genetic correlation with starch concentration and grain weight using two populations in maize (Zea mays L.) - Yuling Li; Yanzhao Wang; Mengguan Wei; Xuehui Li; Jiafeng Fu (Journal of Genetics, 2009)

A mixture model approach to the mapping of QTL controlling endosperm traits with bulked samples - Xuefeng Wang; Zhiqiu Hu; Wei Wang; Yuling Li; Yuan-Ming Zhang; Chenwu Xu (Genetica, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)